On the relation between soil moisture dynamics and the geographical distribution of Culicoides imicola. Issue 2 (25th March 2013) - Peters, Jan; Conte, Annamaria; Van doninck, Jasper; Verhoest, Niko E. C.; De Clercq, Eva; Goffredo, Maria; De Baets, Bernard; Hendrickx, Guy; Ducheyne, Els
ABSTRACT Culicoides imicola is the main biological vector in the transmission of the Bluetongue virus in the Mediterranean basin. Its geographical range is constrained by environmental characteristics, and soil moisture has been proposed as an important constraint because of its effect on C. imicola breeding habitat. The few field studies on breeding habitat of C. imicola indicate the favourability of (semi‐)moist habitat that is not flooded. Data on C. imicola in Calabria revealed the presence of C. imicola at the eastern Ionian coastal area and the absence at the greater part of the western Tyrrhenian coastal area. A spatially distributed soil moisture model was applied to obtain daily soil moisture estimates for Calabria and to assess the relationship between soil moisture and the particular C. imicola distribution at the study region. The temporal soil moisture pattern was not significantly different between locations of contrasting C. imicola occurrence. The monthly average volumetric soil moisture content, however, was found to differ substantially. Soil moisture conditions of the topsoil at locations of C. imicola presence were consistently wetter. Particularly in August, at the onset of the season of high C. imicola abundance, soil moisture was significantly higher at the presence sites and sustained the larval stages of the C. imicola life cycle. This study provides evidence that soil moisture imposes an important constraint on the geographical distribution of C. imicola. Soil moisture may therefore be considered as a key environmental variable for the delineation of suitable C. imicola habitat. Copyright © 2013 John Wiley & Sons, Ltd.